Desarrollo cognitivo en el área de Ciencias Naturales en Educación General Básica Superior de la Unidad Educativa Fisco Misional Juan Pablo II, cantón Loreto provincia de Orellana. - Pino Panchi, Myrian Yolanda (2020)
In the present work, it was determined that cognitive development is deficient in the Natural Sciences Area in Higher Basic General Education of the Juan Pablo II Fiscal Missionary Educational Unit, Loreto canton, Orellana province, caused by low knowledge about cognitive methodologies in teachers, who have oriented their educational work to behaviorism, therefore, the objective is to optimize cognitive development; The research involved the qualitative method, applied through the IN SITU observation of the class performance of 50 students and a survey of 12 teachers from the Natural Sciences Area, the results allowed to structure 7 alternatives aimed at increasing cognitive development, the proposal was rated by 6 experts and 9 users, who gave a median rating of 4.66 which is at the level of excellent, for the use of recyclable materials, relationship with ICT and the ease of application that they will have; The proposal has the acceptability of the teachers, the interest of the students and the approval of the authorities of the Educational Unit; This shows the possibilities of expanding the application of cognitive development in the institution, to achieve a comprehensive training of the student and the continuous use of updated teaching methodologies.